2018
DOI: 10.1128/jvi.00292-18
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 Impairs HIV-1 Gene Expression and Negatively Modulates Reactivation of Viral Latency in CD4 + T Cells

Abstract: Sterile alpha motif and HD domain-containing protein 1 (SAMHD1) restricts human immunodeficiency virus type 1 (HIV-1) replication in nondividing cells by degrading intracellular deoxynucleoside triphosphates (dNTPs). SAMHD1 is highly expressed in resting CD4 T cells, which are important for the HIV-1 reservoir and viral latency; however, whether SAMHD1 affects HIV-1 latency is unknown. Recombinant SAMHD1 binds HIV-1 DNA or RNA fragments , but the function of this binding remains unclear. Here we investigate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…Phosphorylated SAMHD1 is the inactive form of the restriction factor, thus, our observation of decreased levels of pSAMHD1 concomitant with maintenance of the total SAMHD1 availability indicates increased relative expression of the active form of this antiviral factor. SAMHD1 was first shown to restrict HIV-1 in myeloid and dendritic cells [ 51 ] and was recently demonstrated to have an analogous role in macrophages [ 73 75 ] and CD4 T cells [ 76 78 ]. In CD4 T cells, a cyclin-binding motif on SAMHD1 is required for its restriction of HIV [ 79 ] and its regulation by cell-cycle associated proteins including cyclins or Cyclin-Dependent Kinases (CDKs) has been demonstrated [ 54 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated SAMHD1 is the inactive form of the restriction factor, thus, our observation of decreased levels of pSAMHD1 concomitant with maintenance of the total SAMHD1 availability indicates increased relative expression of the active form of this antiviral factor. SAMHD1 was first shown to restrict HIV-1 in myeloid and dendritic cells [ 51 ] and was recently demonstrated to have an analogous role in macrophages [ 73 75 ] and CD4 T cells [ 76 78 ]. In CD4 T cells, a cyclin-binding motif on SAMHD1 is required for its restriction of HIV [ 79 ] and its regulation by cell-cycle associated proteins including cyclins or Cyclin-Dependent Kinases (CDKs) has been demonstrated [ 54 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…After cells were washed with staining buffer and stained with fluorescein isothiocyanate (FITC)-conjugated anti-human IgG (Fc specific) (F9512, 1:100; Sigma-Aldrich) for 30 min, the cells were washed and resuspended with staining buffer and then detected using a Guava EasyCyte flow cytometer (Guava Technologies). The flow cytometry data were analyzed with FlowJo software (version 10; Tree Star) as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, it is plausible that SAMHD1mediated HIV-1 restriction prevents activation of innate and adaptive immune responses, indicating competition between cell-autonomous virus control and viral replication. A recent study reported that SAMHD1-mediated suppression of HIV-1 gene expression negatively affects reactivation of viral latency in CD4 + T cells, suggesting a novel role for SAMHD1 in regulating HIV-1 latency [112]. The function of SAMHD1 in anti-viral immune regulation is complex and connected to multi-cellular pathways.…”
Section: Samhd1 Regulation Of Immunity: Broad Implicationsmentioning
confidence: 99%